2020
DOI: 10.1007/s12350-019-01928-0
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid PET- and MR-driven attenuation correction for enhanced 18F-NaF and 18F-FDG quantification in cardiovascular PET/MR imaging

Abstract: Background: The standard MR Dixon-based attenuation correction (AC) method in Positron Emission Tomography / Magnetic Resonance (PET/MR) imaging segments only the air, lung, fat and soft-tissues (4-class), thus neglecting the highly attenuating bone tissues and affecting quantification in bones and adjacent vessels. We sought to address this limitation by utilizing the distinctively high bone uptake rate constant Ki expected from 18 F-Sodium Fluoride (18 F-NaF) to segment bones from PET data and support 5-clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…TBR 50 gave the best trade-off between increased CNR and reduced DTBR the tracer is taken up) to the adjacent aneurysm. 9,10 Our previous study 17 extensively investigated the spill-in effect in [ 18 F]-NaF PET imaging of AAA, and it was shown that the spill-in effect depends on the activity uptake in the bone, proximity of the aneurysm to the bone, as well as ROI delineation criteria. This effect poses a great challenge to the quantification accuracy at the aneurysm site and it may adversely affect AAA disease prediction and patient management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBR 50 gave the best trade-off between increased CNR and reduced DTBR the tracer is taken up) to the adjacent aneurysm. 9,10 Our previous study 17 extensively investigated the spill-in effect in [ 18 F]-NaF PET imaging of AAA, and it was shown that the spill-in effect depends on the activity uptake in the bone, proximity of the aneurysm to the bone, as well as ROI delineation criteria. This effect poses a great challenge to the quantification accuracy at the aneurysm site and it may adversely affect AAA disease prediction and patient management.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that a major challenge and an inherent limitation of using [ 18 F]-NaF for AAAs is that [ 18 F]-NaF is taken up by the vertebrae because it is mainly a bone radiotracer. 9,10 The anatomical site of the vertebrae is close to the posterior wall of the aorta, which results in an increased signal from this region because of the spill-in effect, leading to inaccurate quantification results. 11 Thus, to increase the accuracy of the results, it is essential to either correct for the spill-in effect or else to identify the most appropriate quantification metrics which are less affected by the spill-in effect.…”
mentioning
confidence: 99%
“…In this point of view, development of PET/CT acquisition with a dual-tracer simultaneous administration of 18 FDG and 68 Ga-DOTApeptides to assess high G2/G3 NETs or neuroendocrine carcinoma would be useful and could allow differentiating non- 68 Ga-DOTApeptides-avid NETs from Ups. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, it has not been implemented in routine practice due to several limitations such as the lack of consensus for dose proportion and the difficulty in separating the signal of both tracers. Recently, a feasibility study has suggested that WB-dynPET could quantitatively extract the two separate tracer kinetics and also analyze different processes [25].…”
Section: Simultaneous Information Collection With Tracer Cocktail Injectionmentioning
confidence: 99%